Effects of foliar spraying with amino acid and potassium fertilizers on the yield and quality of Anji white tea - LUO Lingxun; ZUO Ting; CHENG Wei; ZHU Yongcong; NI Yuemin; LENG Mingzhu; NI Wuzhong (浙江大学学报. 农业与生命科学版)
Cold injury in early spring is one of the main harmful factors affecting the production of spring tea. It is of practical significance to improve the cold resistance and early fresh leaf yield of tea plants by foliar fertilization. In this work, field experiments were conducted to study the effects of foliar spraying with amino acids (AA1, AA2), potassium (K1, K2) and their mixed solution (AA-K1, AA-K2) on the yield and quality of Anji white tea. The results showed that compared with spraying water (CK treatment), foliar spraying with the mixed solution of amino acids and potassium (AA-K1 and AA-K2 treatments) significantly increased the early fresh leaf yield and total yield of Anji white tea (P＜0.05). By observing the ultrastructures of chloroplasts, it was found that the starch granule size in leaves treated with AA-K1 enlarged significantly during the regreening period. The K1 and K2 treatments obviously increased the total chlorophyll content in the leaves of Anji white tea during the pre-albino period and the regreening period, whereas the K2 treatment obviously increased the carotenoid content in the leaves during the pre-albino period, the albino period and the regreening period. The soluble sugar contents of the K2 and AA-K1 treatments were not significantly different, but both were significantly higher than those of the other treatments (P＜0.05). Compared with the CK treatment, the mixed solution of amino acids and potassium (AA-K1 and AA-K2 treatments) increased the total amount of amino acids in the young leaves and significantly increased the catechin content, but the caffeine content was not significantly different. In summary, foliar spraying with the mixed solution of amino acids and potassium (AA-K1 and AA-K2 treatments) can clearly improve the yield of early fresh leaves and improve the young leaf quality of Anji white tea, which has practical reference values for the development of water-soluble fertilizers containing nitrogen, phosphorus, potassium and amino acids.